Modified Media for Fungi Symbiont Sponge Agelas sp. (Fusarium sp.) Cultivation against Multidrug-Resistant Bacteria - Khoeruddin Wittriansyah; Agus Trianto; Ocky Karna Radjasa (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research Fusarium symbiont Agelas sponge has antibacterial activity against aureus and E. coli Multi Drug Resistant Fusarium can grow on modified media soursop juice (SJ) and ginger juice (GJ) and has different inhibitory abilities against bacteria test Fusarium bioactive compounds were analyzed and purified by HPLC Based on TLC visualization, one of the bioactive compounds contained in Fusarium is a steroid group   Abstract Marine symbiont fungi, specifically, are likely to have antibacterial properties. The production of secondary metabolites in cultures is strongly influenced by nutrient availability. This study aimed to study the modified media for the cultivation of Fusarium sp. and its antibacterial bioactivity. Fusarium sp. was isolated from Agelas sp. sponge collected from Riung Sea, East South Nusa, Indonesia. In this study, the modified media was soursop juice (SJ), ginger juice (GJ), and sago (S). The fungal mycelium was cultured and scaled up for 7–14 days until the mycelium achieved maximum growth. A filtration funnel and HPLC were used to purify the bioactive compounds. The diffusion agar method was used to test antibacterial activity against the multi-drug resistant (MDR) Staphylococcus aureus and Escherichia coli. The results indicated that Fusarium sp. could grow on soursop juice and ginger juice but could not grow on sago media. The inhibition zone produced by the filtration fraction of Fusarium sp. from each media differed. The soursop juice media produced the largest inhibition zone against both S. aureus (11.56 mm ± 0.140) and E. coli (12.16 mm ± 0.094) at 100 Î¼g/disc. The ginger juice (GJ) and soursop juice (SJ) media are promising as alternative culture media for Fusarium sp. The structure of the bioactive compound Fusarium sp. from GJ and MJ media culture can be further investigated using NMR.